1990
DOI: 10.1111/j.1365-2265.1990.tb00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose Pituitary Irradiation for Acromegaly

Abstract: External radiotherapy has been used as primary treatment for acromegaly in 29 patients and in combination with surgery in 41 patients in whom growth hormone levels remained elevated postoperatively. Fourteen further patients who did not receive radiotherapy have also been studied, four of whom had undergone surgical treatment. Radiotherapy schedules consisted of 20 Gy in eight fractions over 11 days (n = 23) or 35-40 Gy in 15 fractions over 21 days (n = 47). Growth hormone hypersecretion was either unchanged o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 27 publications
3
32
2
Order By: Relevance
“…This implies that the regimens currently in use for delivering irradiation to the pituitary gland (in terms of fractionation and total dose), have no major adverse effects on brain structures. However, although this is true for the most serious and life-threatening complications, pituitary insufficiency as a result of RT is still reported with increased frequency, with its highest incidence in those patients with the longest follow-up (12,15,22). In the present study, deficiencies in anterior pituitary hormone secretion were only infrequently observed at 5 years following RT.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…This implies that the regimens currently in use for delivering irradiation to the pituitary gland (in terms of fractionation and total dose), have no major adverse effects on brain structures. However, although this is true for the most serious and life-threatening complications, pituitary insufficiency as a result of RT is still reported with increased frequency, with its highest incidence in those patients with the longest follow-up (12,15,22). In the present study, deficiencies in anterior pituitary hormone secretion were only infrequently observed at 5 years following RT.…”
Section: Discussionmentioning
confidence: 60%
“…In the present series, in addition to more strict criteria, achievement of mean GH levels of less than 5 ng/ml was also assessed, in order to allow comparisons to be made with other recently reported series in the literature (13,15). On the basis of this criterion, our reported remission rate is comparable to those reported series with long-term follow-up, with mean GH levels falling to <5 ng/ml in 52-79% of patients at 10 years of followup (10-16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most reports of the effectiveness of EBRT in the treatment of acromegaly have used serum GH concentration as the marker of therapeutic ef®cacy and indicate, in general, a 50% reduction during the ®rst 1±2 years after EBRT, declining further to 25% of the pre-radiotherapy level by 5 years (5,20,21). The chances of achieving`safe' GH levels following EBRT depend largely on the pre-EBRT GH level, with the probability of success signi®cantly greater in patients with pre-EBRT values of 30 mU/l compared with those with GH levels .30 mU/l (22). Long-term data regarding the effectiveness of focussed EBRT, using either a linear accelerator or a gamma knife, are not yet available.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy (RT) is used in the following cases: (a) after surgical resection (combined treatment modality) as recurrence rates are high especially for macroinvasive adenomas (3 -7, 11), (b) recurrence after surgery or irradiation, and (c) as a sole treatment for older or medically inoperable patients or for patients refusing surgery. The dose for optimal tumor control probability is in the range of 45-55 Gy, whereas some authors recommend lower doses for postoperative RT (12). Radiation-induced cerebral necrosis is a very rare complication within this dose range (4)(5)(6)(7).…”
Section: Original Articlementioning
confidence: 99%